Tourism Potential and the Assessment of Tourist Destinations as Basis for the Tourism Sustainable Development - SADYKOV, Zhassulan; TAKHTAYEVA, Rimma; NUSSUPOVA, Larissa; NURMUKHAMEDOVA, Sharipa; AKIMOV, Zhaxylyk (Journal of Environmental Management and Tourism; Vol 14 No 4 (2023): JEMT, Volume XIV, Issue 4(68), Summer 2023, 2023)
Tourism has the potential to provide economic benefits, create employment opportunities, and promote cultural exchange between people from different regions and countries. The development of tourism in a particular destination depends on its tourism potential and the assessment of tourist destinations to ensure sustainable tourism development. The aim of the study is to assess the tourism potential of Kazakhstan as the basis for the development of sustainable tourism, focusing on the Almaty region, taking into account the development of the mountain cluster. During the research study initiated, we analyzed the statistical data of reports on the development of tourism in the resort areas of the Republic of Kazakhstan, and also reviewed valuable scientific papers in the field of sustainable tourism development.